Beyond Religious Identity: Understanding Non-Muslim Decisions to Participate in Sharia Insurance - Abdi Mitro Giripati; Fauzi Arif Lubis; Sri Ramadhani (Jurnal Investasi Islam, 2026)
Sharia insurance has increasingly developed as an alternative financial protection mechanism based on principles of justice, transparency, and mutual assistance. However, previous studies on Sharia insurance adoption have predominantly focused on Muslim consumers and religious-based motivations, providing limited understanding of how non-Muslim consumers perceive and participate in Sharia insurance within a pluralistic society. This study addresses this gap by examining the decision-making process of non-Muslim customers who participate in Sharia insurance and exploring whether their choices are influenced by religious identity or by broader ethical and functional considerations. Using a descriptive qualitative approach, this study conducted in-depth interviews with eight non-Muslim Sharia insurance participants in Medan City, Indonesia, selected through purposive sampling. The findings reveal that non-Muslim participation is primarily shaped by rational, ethical, and utilitarian considerations rather than theological motivations. Internal factors, including financial security motivation, perceived fairness, transparency, educational background, and economic capacity, interact with external factors such as peer influence, product attributes, service quality, promotional communication, and premium affordability in forming consumer decisions. This study advances knowledge by demonstrating that Sharia insurance can transcend religious boundaries and function as an inclusive ethical finance instrument within a multi-faith market. Theoretically, this research contributes to Islamic finance and consumer behavior literature by proposing a shift in understanding Sharia financial adoption from a faith-based consumption perspective toward an ethical-value and inclusive finance perspective. These findings suggest that expanding Sharia insurance acceptance requires emphasizing universal financial values rather than relying solely on religious identity-based marketing strategies.